2014
DOI: 10.5713/ajas.14.0321
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a Worm Leachate as Source of Humic Substances in the Drinking Water of Broiler Chickens

Abstract: The objective of this research was to evaluate the growth performance, the apparent ileal digestibility of nitrogen and energy, the retention of nutrients and the apparent metabolizable energy corrected to zero nitrogen retention (AMEn) in broiler chickens supplemented with increasing doses of a worm leachate (WL) as a source of humic substances (HS) in the drinking water. In Exp. 1, 140 male broilers were penned individually and assigned to four WL levels (0%, 10%, 20%, and 30%) mixed in the drinking water fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 19 publications
1
39
1
2
Order By: Relevance
“…Farm animals are an essential component of this triad because they are exposed to growth promoter antibiotics (GPA) to improve animal health, welfare, and productivity, and act as reservoirs and vectors of resistance genes [1,3]. For this reason, several new additives have been tested as growth promoters to reduce or alternate the inclusion of GPA in feeds, while maintaining an efficient animal production to obtain safe edible products [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Farm animals are an essential component of this triad because they are exposed to growth promoter antibiotics (GPA) to improve animal health, welfare, and productivity, and act as reservoirs and vectors of resistance genes [1,3]. For this reason, several new additives have been tested as growth promoters to reduce or alternate the inclusion of GPA in feeds, while maintaining an efficient animal production to obtain safe edible products [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The main substances that make up the HS are the humic acids (HA), fulvic acids (FA), and humins, and hence, they are a complex mixture of aliphatic chains or aromatic rings with specific content of functional groups, but the concentration of these substances differs according to the raw materials that they originate from [8][9][10]. Leonardite and lignites, two non-renewable resources, are the primary commercial sources of HS, while compost and worm compost, especially those produced with animal manure, are two environmentally friendly sources of HS [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In poultry, several studies indicate that HA have the ability to adsorb mycotoxins and improve performance (Arafat, Khan, & Saima, ; Gomez‐Rosales & Angeles, ; Ji, McGlone, & Kim, ; Van Rensburg, Van Rensburg, Van Ryssen, Casey, & Rottinghaus, ). In addition, several studies have shown that HA reduce emissions of ammonia from the environment (Henderson, ; Ji et al., ; Zralý, Písaříková, Trčková, & Navrátilová, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, due to their adsorbent capacity, HA have been used to reduce mycotoxicosis (van Rensburg et al, 2006;Ghahri et al, 2010;Arafat et al, 2017) and to reduce ammonia emissions from pig manure (Ji et al, 2006;Písaříková et al, 2010). In poultry, several investigators have reported that HA improves performance, gut morphology, carcass traits and meat quality and reduces social stress (Karaoglu et al, 2004;Cetin et al, 2011;Gomez-Rosales and Angeles, 2015). As far as we are aware, this is the first study trying to evaluate the effect of HA extracted from a worm-compost on S. Enteritidis recovery in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest that HA used with proper nutritional, management and biosecurity practices, improve intestinal integrity and performance in poultry (Karaoglu et al, 2004;Ji et al, 2006;Ipek et al, 2008;Gomez-Rosales and Angeles, 2015). Nevertheless, these benefits in animal performance are poorly understood.…”
Section: Introductionmentioning
confidence: 99%